Perspectives of nurses working at COVID-19 wards on professional moral courage: A descriptive study - Mohammad Mahboubi; Akram Salamat; Ali Ebrazeh; Sara Sayar; Zahra Abbasi; Marjan Mardani Hamooleh (Golestan University of Medical Sciences, 2023)
Background: Nurses may be threatened with professional moral courage while providing care to patients with Covid-19. The present study aimed to evaluate the professional moral courage of nurses caring for patients with Covid-19. Methods: This study was a cross-sectional study. In this study, 200 nurses working in COVID wards participated by convenience sampling method. Data collection tools were personal profile forms and valid and reliable tool of professional moral courage. Data were analyzed using descriptive statistics and inferential statistics (ANOVA And T-TEST) under SPSS software version 16. Results: The overall score of nurses' professional moral courage was 56.25±7.02. Other findings of the study indicated that among the personal characteristics of nurses, professional moral courage and organizational position (P = 0.005) and nursing work experience in the COVID ward (P = 0.003) had a statistically significant relationship. Conclusion: Considering the average state of moral courage and the fact that the average score of supervisors is lower than that of nurses, it is obligatory for nursing managers to plan for the promotion of professional moral courage of nurses to face future crises. The most important of these actions can be holding educational workshops with ethical themes for nurses and students so that they can obtain professional moral courage in their profession in more desirable way.